Case report: Drug-eluting bead transcatheter arterial chemoembolization in liver metastasis and retroperitoneal lymph node metastases of renal cell carcinoma: effective local therapy with the first report - Qiu, Zhenkang; Ji, Junjie; Zhang, Shuo; Wang, Song (Frontiers in Oncology, 2024)
The liver is the fourth most common site of metastasis in renal cell carcinoma (RCC), which is usually treated with systemic therapies and local treatments. However, local treatments are challenging in RCC patients with liver metastasis who failed in first-line systemic therapy. Here, we report a case of a patient with both liver-dominant RCC metastasis and recurrence in the operative site who had failed in first-line targeted therapy plus immunotherapy, received drug-eluting bead transcatheter arterial chemoembolization (DEB-TACE), and achieved a complete response.